Aerobic evaluation in soccer. - Juliano Fernandes Da Silva (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
Physical assessments are fundamental for the control and improvement of the performance of soccer players. In this respect, field and laboratory tests are commonly used to evaluate physical fitness in this sports modality. However, it is important to choose the appropriate protocol according to the objectives of the assessment. Thus, the aim of the present study was to perform a critical-narrative review of the aerobic assessment of soccer players, including physiological indices and field and laboratory tests. With respect to the aerobic indices identified in this review, maximal oxygen uptake, anaerobic threshold, and running economy were found to contribute to the development of training programs and help monitor their effects in soccer players. However, the anaerobic threshold is the index most sensitive to the effects of training and also better discriminates performance among athletes of different competitive levels. Regarding field tests, the Carminatti test (Tcar) and Yo-Yo intermittent recovery level 1 (YYIR1) test are the most suitable tests for the aerobic assessment of soccer players considering their specificity, validity and reproducibility. However, the TCar permits the direct transfer of indicators of aerobic power and capacity to the training sessions, whereas the YYIR1 mainly explores the distance covered, which partly limits this transfer.